BAHASA DAN GENDER: KAJIAN KARAKTERISTIK KEBAHASAAN LAKI-LAKI DAN PEREMPUAN DALAM FILM ANAK - Niswatin Nurul Hidayati (LPPM Institut Agama Islam Al-Hikmah Tuban, 2016)
Coates (1996) stated that children learn language by modelling the speech of their community, while simultaneously learning the cultural role that is assigned to them by society depending on their sex. Then, children animated movies as one of modern media became a tool in delivering that kind of message which sometimes contained gender stereotype included in the characters’ speeches. Some linguists belived that men and women have different language features used in their daily conversation. Holmes (1995) stated that the linguistic forms used by women and men contrast - to different degrees – in all speech communities. In his research on Norwich society, he found ut that men mostly used more vernacular language than women. This research aimed to describe the language features used by men and women characters in children animated movies, specifically in Cars and Barbie and 12 Dancing Princesses movies. The research’s results showed that both man and woman characters use language features proposed by Lakoff (1975), such as, empty adjectives, hedge, intensifier, hypercorrect grammar super polite form, tag question, and emphatic stress, even though the characteristics of color words and question intonation have not been found in the characters’ utterances. The difference between men and women’s speeches is shown clearly through the characteristic of hypercorrect grammar in which man used informal speeches in higher frequency than woman. Overall, it can be said that Barbie and 12 Dancing Princesses which was targeted for girls had more formal language variation, while Cars which is targeted for boys had more informal language variation.